Evolution of Regulatory Governance for Human Research in Costa Rica - Ramírez, Karol (Odovtos - International Journal of Dental Sciences, 2025)
Regulatory governance of human research derives from historical abuses of people participating in health related and non-health relates studies. Costa Rica was no exception and nowadays counts with a Regulatory Law of Biomedical Research (Law 9234) that guarantees the protection of research participants’ human rights. The aim of this narrative review is to overview the gradual development and state of the art of protections and oversight of research with humans in Costa Rica. A recapitulation of why regulatory governance for biomedical human research was enacted in 2014 will be discussed. Even so, there is no legal requirement in Costa Rica, as in other developing nations, for non-health related protocols with human participants, to undergo the scrutiny of research boards. Nonetheless, even before Law 9234 was passed, the University of Costa Rica made efforts to compel compliance with research ethics when studying humans. Therefore, another objective is to review the current ethical guidelines dictated by the University of Costa Rica and Scientifical Ethics Committee of the University of Costa Rica to conduct responsible human research. The University of Costa Rica’s institutional regulatory framework on human research, can serve as a model to other national and international institutions from developing nations, where ethical assessment of sociocultural research is relatively neglected, compared to the review of biomedical and clinical studies.